2020
DOI: 10.1016/j.bbih.2020.100171
|View full text |Cite
|
Sign up to set email alerts
|

Identifying evidence informed psychological interventions during the COVID-19 pandemic: Rapid review of the literature

Abstract: Highlights Less than a quarter of psychological interventions are developed based on evidence Evaluation of the effectiveness of existing online mental health resources is required Front-line healthcare providers experienced severe mental distress during COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…One of the greatest changes in mental health treatment has been the move to online treatment during the pandemic, both for traditional open-ended psychological interventions [61] and shorter-term programmes specifically utilised for the pandemic [62]. A previous meta-analysis has shown that remote interventions can be effective in improving psychological wellbeing [15].…”
Section: Discussionmentioning
confidence: 99%
“…One of the greatest changes in mental health treatment has been the move to online treatment during the pandemic, both for traditional open-ended psychological interventions [61] and shorter-term programmes specifically utilised for the pandemic [62]. A previous meta-analysis has shown that remote interventions can be effective in improving psychological wellbeing [15].…”
Section: Discussionmentioning
confidence: 99%
“…The majority agreed that the sessions were intellectually challenging, but the instructors were dynamic, and encouraged students to participate. [32] To determine which of the strategies presented have the potential to benefit FLHCP that are concurrently enrolled in the university.…”
Section: Quantitativementioning
confidence: 99%
“…The study by [28] drew the same conclusions and said chores and distractions at home and poor internet connectivity affected online classes' smooth flow. Healthwise, continuous screen exposure caused eye strain and headaches, while some even suffered from stress and anxiety [32,49].…”
Section: Challenges On Smart Learning Environments Caused By the Pand...mentioning
confidence: 99%